Evaluation of the characteristics of infection prevention and control programs and infection control committees in Brazilian hospitals: A countrywide cross-sectional study. Issue 1 (26th April 2023) - Arns, Beatriz; Agani, Crepin Aziz Jose Oluwafoumi; Sesin, Guilhermo Prates; Horvath, Jaqueline Driemeyer C.; Fogazzi, Débora Vacaro; Romeiro Silva, Fernanda Kelly; Costa, Lauren Sezera; Pereira, Adriano Jose; Nassar Junior, Antônio Paulo; Cavalcanti, Bruno Tomazini; Dietrich, Camila; Veiga, Viviane Cordeiro; et al.
Abstract: Objective: Data are scarce regarding hospital infection control committees and compliance with infection prevention and control (IPC) recommendations in Brazil, a country of continental dimensions. We assessed the main characteristics of infection control committees (ICCs) on healthcare-associated infections (HAIs) in Brazilian hospitals. Methods: This cross-sectional study was conducted in ICCs of public and private hospitals distributed across all Brazilian regions. Data were collected directly from the ICC staff by completing an online questionnaire and during on-site visits through face-to-face interviews. Results: In total, 53 Brazilian hospitals were evaluated from October 2019 to December 2020. All hospitals had implemented the IPC core components in their programs. All centers had protocols for the prevention and control of ventilator-associated pneumonia as well as bloodstream, surgical site, and catheter-associated urinary tract infections. Most hospitals (80%) had no budget specifically allocated to the IPC program; 34% of the laundry staff had received specific IPC training; and only 7.5% of hospitals reported occupational infections in healthcare workers. Conclusions: In this sample, most ICCs complied with the minimum requirements for IPC programs. The main limitation regarding ICCs was the lack of financial support. The findings of this survey support the development of strategic plans to improve IPCs in Brazilian hospitals.